Moderate sedation for elective upper endoscopy with balanced propofol versus fentanyl and midazolam alone: a randomized clinical trial - Levitzky, B. E.; Lopez, R.; Dumot, J. A.; Vargo, J. J. (Endoscopy, 2012)
Background and study aims: Balanced propofol sedation (BPS) combines propofol with opiates and benzodiazepines and targets at moderate sedation. Data comparing outcomes of BPS and standard sedation with opiates and benzodiazepines during elective esophagogastroduodenoscopy (EGD) are sparse. The primary end point of this study was to compare, in the recovery area, patient satisfaction with EGD following BPS versus standard sedation.Patients and methods: Prospective, single-blinded randomized trial in 110 outpatients undergoing elective EGD and randomized 1:1 to BPS or standard sedation. Upon full recovery, the primary outcome of patient satisfaction was assessed using a 100-mm visual analogue scale (VAS) (1 = not at all satisfied, 100 = completely satisfied). Sedation recovery times and recall of pain and gagging (1 = none, 100 = severe) were also evaluated using a VAS.Results: The BPS and standard sedation groups were similar regarding American Society of Anesthesiologists (ASA), Mallampati class, age, sex, and body mass index (BMI). Compared with the standard sedation arm, the BPS group exhibited higher median procedural satisfaction (99 vs. 85, P < 0.001), and lower median scores for recall of pain (P < 0.001) and gagging (P < 0.001). BPS resulted in a shorter median recovery time (min) (11 vs. 23, P < 0.001). On multivariable regression analysis, predictors of patient satisfaction included use of propofol, increased age, and higher fentanyl dosage.Conclusions: BPS targeted to moderate sedation by adequately trained endoscopists results in superior patient satisfaction and shorter recovery times than standard sedation alone during EGD.